Les relations extérieures de l’halieutique japonaise - Doumenge, François (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
Japan's distant seafishing industry provides opportunities for supergains, y et it still remains dependent on the internal market. Its activities which are directed by the State, and implemented by the large industrial and commercial enterprises, are part of the whole evolution of the traditional corporations of the Kumiai. A study of the political, technical, and economical conjuncture and balance of power at the international level show three important periods. 1904-1941 : The imperialistic policy of the military-industrial complex supports the operations of the large enterprises. Between 1933 and 1940, Japan has several hundreds of fishing plants along the coasts of the Russian Far East; factory vessels are used for the canning of salmon and crabs in the Sea of Okhostk and the Behring Sea, and for whaling in the Antarctic and North Pacific ; industrial trawling is carried on along the coasts of the Asian continent while numerous enterprises are set up in Indo-Malaysia for coastal tuna fishing. 1948-1973 : Within the framework of the reconstruction of its economy, Japan at first resumes the same campaigns as those of the pre-War period; to these are added drifting long line fishing of tuna in the intertropical grounds and a powerful industrial trawling in North Pacific. By 1960, these activities are curtailed due to regulations imposed by USSR, USA, and the International Whaling Commission for stock protection. And then there are new competitors (Taiwan, South Korea). A general fail off after 1965 is partly compensated by the industrial trawling in the Behring Sea. 1974-1986: Significant geopolitical and economic changes force Japan to define and to redeploy its foreign fisheries. Pressured by waterside States, Japan gradually withdraws from traditional fishing grounds and endeavours to find new resources in waters which have remained international so as to maintain a balance with its internal market (tuna drifting long lines and seiners, squid fishery). New technology and profits from the internal market allow the industrial armaments to keep their competitive edge. The State strongly supports this sector through its diplomacy and the provision of funds for research and redeployment and by planning the integration of the distant fishing industry within the economical and social development of the traditional fishing cells of the Archipelago.